THE PROSECUTION OF MYANMAR IN INTERNATIONAL CRIMINAL COURT (ICC) OVER FORCE DEPORTATION OF ROHINGYA TO BANGLADESH - Akbar Hazzanna; M. Ya’kub Aiyub Kadir (Fakultas Hukum Universitas Syiah Kuala, 2020)
Abstract - Crime against humanity is one of the big problems happening in the world right now, so it would need all parties to prosecute those who committed such crimes. One of the crimes against humanity that happening now is in Myanmar, which is called ‘force deportation’ of Rohingya people to Bangladesh. Many Rohingyas were killed by Myanmar authorities, in 2017 among 600.000 Rohingyas were killed and force deported to Bangladesh, a neighbouring state. Consequently, in 2018 the ICC prosecutors initiate to prosecute Myanmar, despite it is not a party to the 1998 Rome Statute. The purpose of this study is to investigate the extent to which Myanmar to be tried in an international court because Myanmar is not a member of the Rome Statute 1998. In more specific this study aims to see the legal basis that can be used to prosecute Myanmar for crimes against humanity of force deportation they committed. This study mainly utilised a doctrinal (normative) methodology and case study approach which is Myanmar case in the ICC. Such study has been considered within international criminal law field. The process of collecting data is done by collecting information from ICC Website, International Criminal Law books, related journals, and other materials from the internet. This study found that the ICC prosecutor has firmly found a legal ground of force deportation as an element of crimes against humanity which has been reflected to an international boundary which can be rid of traditional scope of jurisdiction over state party to the 1998 Rome Statute. Moreover, from such a breakthrough another possibility to prosecute Myanmar from the other crimes against humanity such as genocide, may also feasible. As the prosecution process remains ongoing, this research can contribute to be starting accumulation of knowledge on this issue, and hopefully be continued by other researchers in future. Keywords : Force Deportation, International Crimes, Rohingya.